The novels of V Nabokov: psycholinguistic features in fiction of the XX century - Bazhanova, Helene (2019)
Studying Vladimir Nabokov’s works, we have been convinced of the continuity of the social codes, beginning with antiquity (there is a special place for mythology in Nabokov’s creative works), and ending with the XX century. However, in our opinion, the most powerful influence was exerted on the writer by the cultural traditions of Europe, especially by literature of the XIX century. It is not possible to study all the aspects of the continuity, so within the framework of this article we have considered the most important ones, which, due to the continuity, acquire a deeper philosophical meaning and an additional connotation.We analyzed the existing themes, motives and images in V. Nabokov's creative works, and we saw the influence of F. Nietzsche, A. Bergson, M. Proust and D. G. Lawrence on the artistic method of the writer.